(untitled) (Research, Society and Development, 2026)
The impact of sugarcane management practices on the three-dimensional architecture of soil morphology was quantitatively assessed using complex network analysis of soil images obtained through X-ray computed tomography (CT). This study aims to examine the impact of land-use changes on soil structure by applying the Horizontal Visibility Graph (HVG) method to 3D X-ray computed tomography images of soil samples from the Atlantic Forest and a sugarcane plantation. The HVG method proved effective in characterizing structural changes in the soil samples. Topological indices Clustering Coefficient, Average Shortest Path Length, and Average Degree of the HVG networks, were calculated and found to be correlated with key phenomenological aspects of soil. Among these, the Average Shortest Path Length emerged as the most suitable indicator for quantifying the degradation of soil morphological properties associated with vegetation cover change. Specifically, the transition from Atlantic Forest to sugarcane was shown to alter soil morphology toward greater homogeneity. Overall, these findings demonstrate a clear relationship between the complexity of 3D soil image HVG networks and soil physical properties, highlighting the potential of this approach to quantify soil morphological degradation resulting from land cover change.